2002
DOI: 10.4267/dechets-sciences-techniques.2339
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation expérimentale de l’émission d’oxydes d’azote dans l’incinération des déchets ménagers en four à grilles

Abstract: In front of a deposit of waste in constant evolution, the incineration became a very interesting alternative within the fields of management of waste. Nevertheless the combustion is generative of polluting, notably gas among whom nitrogen oxides. The study of the mechanisms of formation of these species shows a very strong dependence of their yield face to face of the local level in oxygen. So, our study was led to determine the influence of the excess air on the formation of NOx during the incineration of mun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Municipal waste characterisations in France had showed that plastics materials are made with 91% of poly ethylene (P.E.T.) and 9% of polyamide 6 -6 [17]. Specials consist of plastics films and their polymers.…”
Section: The Waste Model Drawingmentioning
confidence: 99%
See 1 more Smart Citation
“…Municipal waste characterisations in France had showed that plastics materials are made with 91% of poly ethylene (P.E.T.) and 9% of polyamide 6 -6 [17]. Specials consist of plastics films and their polymers.…”
Section: The Waste Model Drawingmentioning
confidence: 99%
“…It consist of a cylinder slightly inclined (17), to which is appended the primary burner noted burner 1 (RG1). This cylinder have a diameter of 88 cm, measure 108 cm in length, is suspended on bearings ball which allow its rotation around its axis of symmetry as depicted in Figure 1.…”
Section: The Rotary Kilnmentioning
confidence: 99%
“…This program ("Reactor"), specific to this application, was developed by [10] and optimized by [8]. He had to be repeated and modified to apply to our study.…”
Section: Principle Of the Program Reactormentioning
confidence: 99%